Stretchable motion memory devices based on mechanical hybrid materials - Liu, Yaqing (2020)
Animals possess various functional systems such as sensory, nervous, and motor systems, which show effective cooperation in order to realize complicated and intelligent behaviors. This inspires rational designs for the integration of individual electronic devices to exhibit a series of functions, such as sensing, memory, and feedback. Inspired by the fact that humans can monitor and memorize various body motions, a motion memory device is developed to mimic this biological process. In this work, mechanical hybrid substrates are introduced, in which rigid memory devices and stretchable strain sensors are integrated into a single module, which enables them to work cooperatively in the wearable state. When attached to the joints of limbs, the motion memory device can detect the deformations caused by limb motions and simultaneously store the corresponding information in the memory device. This work would be valuable in materials design and electronics technology toward the realization of wearable and multifunctional electronic modules.